2017
DOI: 10.1007/s00431-017-2881-4
|View full text |Cite
|
Sign up to set email alerts
|

Regular energy drink consumption is associated with the risk of health and behavioural problems in adolescents

Abstract: Adolescents drinking energy drinks are at risk of a wide range of negative outcomes and should be specifically addressed by preventive interventions. What is Known • Energy drink consumption has become popular and frequent among adolescents across Europe. • There is growing evidence that energy drink consumption is related to negative social, emotional and health outcomes, but only a few studies have explored this relationship in adolescents. What is New • Regular energy drink consumption was more frequent amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 38 publications
6
36
1
Order By: Relevance
“…For example, in a nationally representative sample of U.S. middle- and high-school students, significant associations were found between ED frequency and 30-day frequency of use of alcohol, cigarettes, marijuana, or amphetamines ( 32 ). This echoes cross-sectional results among adolescent regular consumers (>1 ED/week) in Europe who were more likely to smoke and drink alcohol compared to non-consumers ( 35 ). Some studies have additionally found evidence for an association between ED consumption and mental health, including stress, anxiety, depressive symptoms, and suicidal ideation, plan or attempt ( 33 , 36 , 37 ).…”
Section: Health Effects Of Edsupporting
confidence: 77%
See 2 more Smart Citations
“…For example, in a nationally representative sample of U.S. middle- and high-school students, significant associations were found between ED frequency and 30-day frequency of use of alcohol, cigarettes, marijuana, or amphetamines ( 32 ). This echoes cross-sectional results among adolescent regular consumers (>1 ED/week) in Europe who were more likely to smoke and drink alcohol compared to non-consumers ( 35 ). Some studies have additionally found evidence for an association between ED consumption and mental health, including stress, anxiety, depressive symptoms, and suicidal ideation, plan or attempt ( 33 , 36 , 37 ).…”
Section: Health Effects Of Edsupporting
confidence: 77%
“…Sleep dissatisfaction, tiredness/fatigue, late bedtime, headaches, stomachaches and irritation ( 35 , 56 59 )…”
Section: Health Effects Of Edmentioning
confidence: 99%
See 1 more Smart Citation
“…We used data from the Health Behaviour in School-aged Children (HBSC) study conducted in 2018 in Slovakia. More detailed information about two-step sampling process and procedure used to acquire this nationally representative sample could be found in our previously published paper [1,31]. In the first step, 140 larger and smaller elementary schools located in rural as well as urban areas from all regions of Slovakia were asked to participate.…”
Section: Sample and Proceduresmentioning
confidence: 99%
“…The worldwide consumption of these drinks increased dramatically over the last decade because they have been marketed as a way to improve alertness and to reduce fatigue among adolescent and adults [2] . Negative health effects of short and long term consumption of EDs have been reported as aggressive behavior, low academic achievement, headache, irritation, tiredness and dissatisfaction to sleep [3] .…”
Section: Introductionmentioning
confidence: 99%